Kedudukan Hukum Akta Perdamaian Sebagai Sarana Penyelesaian Sengketa Bagi Para Pihak Diluar Pengadilan - Mursani Mursani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This study examines The Legal Position of the Peace Deed as a Means of Dispute Resolution for Parties Outside the Court, focusing on the notary’s authority and the legal strength of the peace deed compared to court decisions. Using a normative juridical method, this research emphasizes an analysis of positive legal provisions such as the Indonesian Civil Code, the Notary Law, and the Law on Arbitration and Alternative Dispute Resolution. The findings indicate that notaries possess legal authority to draft peace deeds as authentic instruments ensuring legal certainty and justice for disputing parties. A peace deed made before a notary holds the same legal force as a court decision with permanent legal effect (inkracht van gewijsde) and may serve as an executorial title when issued in the form of a grosse acte. Thus, the notarial peace deed functions as an effective, efficient, and equitable legal instrument for resolving disputes, reinforcing the principles of simplicity, speed, and low cost within the national legal system.